Motivational Factors Affecting Undergraduate Students' Reading Interest - Rena Rahmawati; Anisa Mbali Amah; Astriana Vidia Jerina; Maya Rizki Amayasari (IJET (Indonesian Journal of English Teaching), 2022)
The purpose of this research is to find out factors that affect undergraduate students' lack of motivation in reading. This research only focuses on the surface of the lack of motivation, this research doesn't find the deeper reason. The subject of this study was undergraduate students of IKIP BUDI UTOMO Malang in the English Education Department 2019, A class. The subject was 20 undergraduate students. To collect the data, the researchers used questionnaires and interviews. The use of questionnaires was intended to reveal written data and the interview was unstructured. After distributing the questionnaire, researchers found out that there are few factors affecting undergraduate students lack of motivation in reading. 55% undergraduate students have an average opinion about reading in their spare time, 75% read less than 1 hour everyday and 60% like to read novels. Most of the respondents' motivation to read is to spend time. 43% of the respondents have neutral opinions about whether friends, lecturer or mood have influenced them. And the most obvious obstacle according to the respondents is laziness.